Analisis Spasial Kejadian Penyakit ISPA Ditinjau Dari Lingkungan Fisik Daerah Permukiman Wilayah Desa Prambontergayang Kabupaten Tuban - Herning Setiyani; Tiwi Yuniastuti; Beni Hari Susanto (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
The distribution of Acute Respiratory Infections (ARI) varies across regions, highlighting the need to consider spatial factors and the physical environment of residential areas, including housing density, ventilation size, and waste management, which critically affect community quality of life. This study aimed to conduct a spatial analysis of ARI incidence in relation to the physical residential environment in Prambontergayang Village, Tuban Regency. A quantitative descriptive design with cross-sectional observation was applied, utilizing spatial modeling through geoprocessing techniques such as buffering, overlay, and Nearest Neighbor Analysis (NNA). The study included all 150 houses in the village, selected using purposive sampling. Data were analyzed using the Contingency Coefficient C test and geoprocessing. Findings indicated a clustered pattern of ARI cases, with 34.0% occurring among adolescents and 58.0% among females. Housing density met health standards in 63.3% of cases, ventilation size in 67.3%, and environmentally friendly household waste management in 56.7%. Significant associations were found between ARI incidence and housing density (p = 0.002), ventilation size (p = 0.000), and waste management (p = 0.000). The study concludes that environmental vulnerabilities related to housing density, ventilation, and waste management contribute to ARI incidence. Promoting clean and healthy living practices, adequate nutrition, environmental hygiene, and indoor air quality is essential for ARI prevention and control.